2001
DOI: 10.1002/1529-0131(200111)44:11<2477::aid-art427>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Do silicone breast implants cause rheumatologic disorders?: A systematic review for a Court-Appointed National Science Panel

Abstract: Objective To assist in evaluating expert testimony and scientific evidence presented in law suits brought against silicone breast implant manufacturers, a US District Court Order established a National Science Panel to assess whether existing studies provide scientific evidence of an association between silicone breast implants and systemic classic/accepted connective disease, atypical connective disease, and certain signs and symptoms identified by plaintiffs in the law suits. Local disorders potentially asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 31 publications
1
46
1
2
Order By: Relevance
“…In addition, we analysed antibodies against polymerized acrylamide, which was originally developed for the diagnosis of fibromyalgia and reactions to foreign materials [22]. Although previous studies analysing several systemic immunologic parameters failed to provide unequivocal proof of an association between rheumatologic diseases and silicone contact, those studies did not analyse sICAM-1, APA, Pro III or CIC [12,[23][24][25], which we found to be altered in various groups of SMI patients.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, we analysed antibodies against polymerized acrylamide, which was originally developed for the diagnosis of fibromyalgia and reactions to foreign materials [22]. Although previous studies analysing several systemic immunologic parameters failed to provide unequivocal proof of an association between rheumatologic diseases and silicone contact, those studies did not analyse sICAM-1, APA, Pro III or CIC [12,[23][24][25], which we found to be altered in various groups of SMI patients.…”
Section: Discussionmentioning
confidence: 98%
“…[2][3][4] In addition to these local phenomena, several case reports of systemic autoimmune disease (scleroderma, rheumatoid arthritis, or lupuslike symptoms) and musculoskeletal disorders have been published. [13][14][15][16][17][18][19][20][21][22][23] Despite the widespread use of silicone implants, there have been few systematic studies on the immunologic effects of silicone in humans. 6,20,24 -27 The purpose of our study was to investigate the distribution of immune cells in peripheral blood samples of patients with silicone breast implants and to understand whether silicone induces only the formation of foreign body granulomas as a local reaction or gives rise to subsequent systemic immune reactions as well.…”
mentioning
confidence: 99%
“…[1][2][3][4] Although mortality from breast cancer among women with breast implants has been assessed in some studies, only two studies to date have evaluated the overall mortality pattern of breast implant recipients. 5,6 The overall risk of death for women with breast implants was decreased (standardized mortality ratio [SMR], 0.7; 95% confidence intervals [CI], 0.6 -0.8) in one study 5 and elevated in the other (SMR, 1.5; 95% CI, 1.2-1.8); 6 both studies reported an increased risk of death from suicide.…”
mentioning
confidence: 99%